ELABORASI PENYUSUNAN LAPORAN KEUANGAN KONSOLIDASI KE DALAM NILAI SYARIAH ISLAM - Bambang Waluyo; Ali Masjono (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2012)
This study aimed to obtain a design of the process of preparing the consolidated financial statements associated with syariah values in Islam, especially the value of fairness and honesty. The consolidated financial statements are designed to present the results of operations and financial position of the company and its subsidiaries. In the process, it will be clearly seen an effort to avoid injustice and dishonesty, because things are